Genome-wide analysis of the cellulose synthase gene family in autopolyploid sugarcane (Saccharum spontaneum) - Wei, Xiaoshuang; Wei, Zesheng; Yang, Mingchong; Chen, Qiang; Wang, Jingzhen; Zhao, Liyan; Zhang, Xia; Wang, Lingqiang; Hu, Lihua (Frontiers in Plant Science, 2025)
Sugarcane is the most critical sugar and bioenergy crop. Cellulose synthase (CESA) genes are involved in cellulose synthesis, playing a significant role in plant growth and development, as well as in secondary metabolism. In this study, we systematically analyzed the CESA gene family in Sugarcane (Saccharum spontaneum), recognizing 30 members. 32 pairs of segmental duplication events contributed mainly to the expansion of this superfamily. In addition to plant hormones, stress-responsive and growth-related cis-acting elements were identified in SsCESA gene promoters, along with many MYB, NAC, and WRKY transcription factor binding sites. Transcriptomic data showed that most SsCESA transcripts were higher in stems and leaf transitional parts. qRT-PCR assays confirmed that SsCESA genes could respond to cold, heat, and salt stress. GFP subcellular localization assays exhibited that SsCESA4 and SsCESA9 proteins were localized at the Golgi apparatus. Finally, EMSA experiments confirmed that SsNST1 could bind to the promoters of SsCESA4, SsCESA7, and SsCESA9. This research elucidates the evolutionary patterns and functional characteristics of the SsCESA gene family in sugarcane, providing a basis for future investigations into its mechanism of action.